Results convergence of pharmacopoeial tests by titrimetric methods: acceptance criteria and experimental parameter - Чикалова, Світлана Олегівна; Гризодуб, Олександр Іванович; Бевз, Олена Валеріївна; Зінов'єва, Ірина Григорівна; Кобець, Галина Вікторівна (ScienceRise: Pharmaceutical Science, 2016)
Quality assurance of test results is one of the topical issues of analytical laboratories functioning. Scientifically reasonable criteria and recommendations in relation to the scheme and quality control of pharmacopoeial tests results by volumetric titration methods were developed by the authors according to the previous studies results. The criteria were elaborated by results of test uncertainty estimation. Aim of research was experimental verification of the requirements to results repeatability of pharmacopoeial tests by titrimetric methods developed on the basis of the scientific reasoning. Methods. Authors used the statistical analysis methods of chemical experiment results. Results. Experimental data of the test results by titrimetric methods, obtained in a separate laboratory and in an interlaboratory experiment, were examined. The displayed results belong to the most wide spread pharmacopoeial titration methods for substances: titration with the perchloric acid solution in acetic acid with the visual fixing of end point; potentiometric titration with perchloric acid solution in acetic acid, potentiometric titration of halogen salts of organic bases by the difference of volumes between two potential leaps; aqueous titration with the visual fixing of end point; potentiometric titration with aqueous titrant. Requirements to convergence, elaborated by results of the uncertainty test estimation of titrimetric methods, meet the examined data main parameters. Relevant amount of simultaneous tests, that will be sufficient for the achievement of the recommended values for relative standard deviation of the mean folds, is middle from three to four. Conclusion. The acceptability criteria developed on scientific reasoning basis meet the main parameter of titrimetric methods tests and can be recommended for the use in- functioning of pharmaceutical analytical laboratories